(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aims to test the non-linear relationship between working capital and financial performance by applying it to manufacturing companies listed in Amman Stock Exchange. The sample included 10 manufacturing companies listed in Amman Stock Exchange over the period 2016 - 2020. Working capital was measured by cash conversion cycle, and financial performance by return on assets. The results revealed a non-linear relationship between working capital measured by cash conversion cycle and financial performance measured by return on assets.